PMM.57 Fanconi Anaemia complicating pregnancy – treatment and management of critical thrombocytopenia and anaemia. (9th June 2014) - Scarr, C; Treharne, A; Conner, C; Rayment, R
Abstract : Aim: To understand the underlying pathology and antenatal, intrapartum and postnatal issues associated with Fanconi anaemia, and to appreciate the importance of care planning and MDT working. Discussion: Described first in 1927, Fanconi anaemia is one of an autosomal recessive group of inherited bone marrow failure syndromes. It is characterised by dysmorphic features, pancytopenic bone marrow failure, and susceptibility to certain malignancies. It can be associated with delayed puberty, primary infertility and premature menopause, with limited data on pregnancy management. We present a case of a 23 year old primigravida with pre-existing Fanconi Anaemia. She was known to have severe thrombocytopenia and anaemia, both transfusion dependent. Despite relative stability pre-pregnancy her obstetric course was complicated by superimposed pre-eclampsia and worsening pancytopenia. Issues were further complicated by ceasing her pre-pregnancy androgens which had maintained her platelet count. Antenatal care was managed in a specialist joint haematology clinic with support from national centres and the local blood transfusion service. Additionally potential fetal implications of Fanconi anaemia were considered with the neonatology team. Considerable thought and planning was given to her mode of delivery and intrapartum blood product requirements. The risks and benefits of operative vs. vaginal delivery were debated, with elective Caesarean Section chosen. Post pregnancy follow up included detailed discussion of future contraception leading to hysteroscopic sterilisation. Conclusion: Fanconi anaemia presents many fetal and maternal challenges to the management of pregnancy. Managing rare complex cases such as this not only requires detailed planning but also excellent inter-disciplinary team communication.